Cerebrovascular blood pressure autoregulation monitoring and postoperative transient ischemic attack in pediatric moyamoya vasculopathy. Issue 2 (5th December 2017) - Lee, Jennifer K.; Williams, Monica; Reyes, Michael; Ahn, Edward S.
Summary: Background: Children with moyamoya vasculopathy are at high risk of perioperative cerebral ischemia or hyperperfusion. Maintaining blood pressure within the range of functional cerebrovascular blood pressure autoregulation might reduce the risk of perioperative neurologic injury. Aims: We tested whether blood pressure autoregulation is associated with postoperative transient ischemic attack in a study of patients with pediatric moyamoya vasculopathy. Methods: We conducted an observational study of 15 pediatric patients undergoing surgical revascularization with pial synangiosis. Nine patients had bilateral moyamoya and 6 had unilateral moyamoya. We measured autoregulatory vasoreactivity intraoperatively and during the first postoperative night with the hemoglobin volume index, a value derived from near‐infrared spectroscopy. We also identified the optimal mean arterial blood pressure at which autoregulation was most robust in each patient. Results: Of the 15 children monitored, 3 with bilateral moyamoya and one with unilateral moyamoya experienced a transient ischemic attack. Poorer autoregulation during surgery was associated with postoperative transient ischemic attack among those with bilateral vasculopathy ( P = .048, difference in hemoglobin volume index medians: 0.023, 95% confidence interval: 0.003‐0.071). This relationship was not observed with postoperative autoregulation. The optimal mean arterial blood pressure was identifiable during surgery in all monitored patients, varied among patients, and often differed between the intraoperative and postoperative periods. Conclusion: Dysfunctional intraoperative autoregulation may increase the risk of TIA in patients with pediatric moyamoya vasculopathy. The blood pressure range that supports autoregulation appears to vary among patients. Using autoregulation monitoring to guide individualized blood pressure goals should be studied as a potential method to reduce perioperative neurologic morbidity in pediatric patients with moyamoya.